Predicting the Permanent Safe Donor Area for Hair Transplantation in Koreans with Male Pattern Baldness according to the Position of the Parietal Whorl - Park, Jae Hyun; Na, Young Cheon; Moh, Jae Seong; Lee, Seung Yong; You, Seung Hyun (Archives of Plastic Surgery, 2014)
Background The most crucial factor in hair transplantation for male pattern baldness (MPB) patients is the efficient utilization of the donor-recipient ratio. However, there is no known factor that scientifically predicts the rate of progression of alopecia or indicates a permanently safe donor area.Methods The study considered 1,008 Korean adult males with MPB; of these, it excluded 56 males with an absence of parietal whorls (PWs). The authors investigated the distance from the vertical bimeatal line (VM) to the PW, from the PW to the upper border of the helical rim (HR), and the distance from the PW to the occipital fringe (OF) in 952 subjects with a PW. Furthermore, we examined the distance from the PW to the OF considering the duration of alopecia and age in 322 subjects with vertex alopecia.Results The distance between the VM and PW varied from 1.5 to 11 cm, with an average distance of 6.25 cm. The PW-HR distance ranged from 3.4 to 17.5 cm, and the average distance was 7.79 cm. The PW-OF distance ranged from 0.5 to 5.5 cm, and the average distance was 2.37 cm.Conclusions For the PW, very large variations existed in the vertical direction. The position of the PW could predict the progression range of the total alopecia of the vertex. Alopecia mostly progresses within 6 cm of the PW toward the occipital side.
Keywords: Alopecia; Hair follicle; Transplant donor sites